Sulphur Compounds: Comparison of Different Sorbent Tubes for Their Detection - Elisa Polvara; Eva Gallego; Marzio Invernizzi; Jose Francisco Perales; Selena Sironi (Chemical Engineering Transactions, 2022)
Different techniques have been developed for the analysis of gaseous sulphur pollutants, to maximize the analytical signals. In a complex matrix, such as odorous emissions, the detection of sulphur compounds can be critical in GC analysis, due to the lower concentration of these pollutants and the disturbing effect of co-eluting hydrocarbons. However, their detection is fundamental because they have a non-negligible odour impact. In the field of gaseous emissions analytics, it is common to use sorbent tubes for the sampling step. This technology uses different adsorbent materials, with different selectivity depending on the nature of the gas to be analysed. This work aims to evaluate the ability of three different sorbent tubes to collect different sulphur compounds, belonging to the classes of mercaptans, thioethers and aromatic heterocyclic compounds. A standard solution of 10 sulphur compounds was prepared by diluting in methanol 50 µL of each liquid standard into a 10 mL ?ask. Subsequently, this solution was diluted in methanol to obtain sulphur standards at five different concentrations (approximately 5-500 ng/µL). The tubes were loaded with the standard solutions with an aliquot of each solution, using a gas chromatograph packed column injector and subsequently analysed by TD-GC-MS. By the results obtained - average Response Factor (RF) and its Relative Standard Deviation (% RSD), it is possible to conduct a comparison among these tubes and evaluate their performance. From the comparison of the tubes, discussing % RSD, it is possible to highlight a slightly better performance, in terms of the number of compounds with % RSD = 30%, for tubes specific for sulphur compounds. Focusing on RF values, multi-sorbent bed tubes show slightly higher RFs for very volatile sulphur compounds, but Sulphur tubes present higher RF values for 6 compounds out of 10 compounds considered. The performance of Tenax TA tubes, instead, appears strictly correlated with the compound’s volatility and therefore they don’t appear useful for sorption of very volatile compounds.